Nutritional Status of Children Under Five Years in a Tertiary Care Center: A Cross-Sectional Study - Chand, Barat; Poudel, Drishti; Shrestha, Anil; Thakuri, Pushpa Chand; Thapa, Madhu; Shahi, Anita (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Malnutrition remains a leading cause of under-five mortality globally and in Nepal, with significant rates of stunting, wasting, and underweight. Despite national progress, child nutrition challenges persist, especially among vulnerable groups in hospital settings. This study assesses the nutritional status of children under five attending a tertiary care center in Nepal. Methods: This descriptive cross-sectional hospital-based study was conducted among 260 under-five children attending the Pediatric Department of Nepal APF Hospital, from February to June 2025, after ethical approval (Reference number: NAPFH-031/2024). Data were collected through face-to-face interviews with caregivers and anthropometric measurements. Nutritional status was assessed using WHO standards. Descriptive statistics, chi-square test, and logistic regression were used for analysis. Results: Among 260 children under five years, the overall prevalence of malnutrition was 30%, including 10% stunted, 11.20% wasted, and 15.40% underweight. Malnutrition was significantly associated with the child’s age (p<0.001), with children below 24 months more likely to be malnourished. Father’s education level also showed a significant association (p = 0.005), where lower paternal education correlated with higher malnutrition rates. No significant associations were observed between maternal, environmental, or child-rearing characteristics and the outcome. Conclusions: The present study found a notable burden of malnutrition among under-five children visiting a tertiary care center in Kathmandu with younger age and father’s education significantly associated with malnutrition. Targeted early-life nutritional interventions and improved parental education can help to improve the nutritional status of under five children.